2015
DOI: 10.3791/52983
|View full text |Cite
|
Sign up to set email alerts
|

Selective Depletion of Microglia from Cerebellar Granule Cell Cultures Using L-leucine Methyl Ester

Abstract: Microglia, the resident immunocompetent cells of the CNS, play multifaceted roles in modulating and controlling neuronal function, as well as mediating innate immunity. Primary rodent cell culture models have greatly advanced our understanding of neuronal-glial interactions, but only recently have methods to specifically eliminate microglia from mixed cultures been utilized. One such technique -described here -is the use of L-leucine methyl ester, a lysomotropic agent that is internalized by macrophages and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…We noted several examples of IB4 + phagocytes in close proximity to cultured pFTAA + neurons and some internalization of pFTAA + aggregates ( Figure 4C ). To examine whether endogenous phagocytes were responsible for the loss of tau aggregate-containing neurons that occurs over 2–3 weeks, we eliminated the phagocytes by treatment (4 hr) with leucine methyl ester (LME) ( Jebelli et al, 2015 ), followed by an overnight incubation to ensure death of phagocytes. We found that ~90% of the pFTAA + neurons were maintained after phagocytes were eliminated from the cultures, whereas only ~70% of the neurons remained in untreated cultures after 14 days ( Figure 4D ; p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…We noted several examples of IB4 + phagocytes in close proximity to cultured pFTAA + neurons and some internalization of pFTAA + aggregates ( Figure 4C ). To examine whether endogenous phagocytes were responsible for the loss of tau aggregate-containing neurons that occurs over 2–3 weeks, we eliminated the phagocytes by treatment (4 hr) with leucine methyl ester (LME) ( Jebelli et al, 2015 ), followed by an overnight incubation to ensure death of phagocytes. We found that ~90% of the pFTAA + neurons were maintained after phagocytes were eliminated from the cultures, whereas only ~70% of the neurons remained in untreated cultures after 14 days ( Figure 4D ; p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…; Jebelli et al . ), in the absence of growth factor supplementation. Therefore, the presence of growth factors during the culture period and initial contact with other glia may contribute to the differences in astrocyte glutamate phenotypes between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia present in the ENGCs were depleted with 25 mM leucine-methyl-ester (LME), as previously described ( Jebelli et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, ER stress can also mediate upregulation of pro-inflammatory cytokines ( Chen et al, 2013 ), suggesting the possibility of a self-perpetuating mechanism of detrimental signaling in neurodegenerative diseases centered on ER stress and aberrant, or chronic, inflammatory signaling. With this in mind, we aimed to identify if exposure to FG modulated inflammatory signaling and subsequent neuronal toxicity in a well-characterized in vitro neuronal cell culture model, which can be pharmacologically manipulated to eliminate the presence of microglia ( Piers et al, 2011 ; Jebelli et al, 2015 ). Here, we identify for the first time, a FG-induced increase in neurotoxicity via a non-cell autonomous mechanism involving a microglial TNFα-mediated induction of neuronal ER stress signaling.…”
Section: Introductionmentioning
confidence: 99%